The geohydrology of the Swartkops River Basin : Uitenhage Region, Eastern Cape - Maclear, Limont Gordon Alexander (Department of Geological Sciences, 2017)
A hydrocensus of all groundwater users in the Swartkops River Basin was conducted in 1992 and 1993 to assess the occurrence and quality of groundwater in the Basin, as well as the characteristics of the various aquifers in the Basin. The extent of pollution of the groundwater reserves was noted. This specialist study was carried out to assist the Department of Water Affairs and Forestry in formulating a water quality management plan for the river basin, and was prompted by concern regarding the deteriorating water quality of the region. It was determined that the only aquifer in the river basin which was severely polluted in places was the Swartkops River Alluvial Aquifer. Following recommendations arising from the initial survey, a groundwater monitoring network of shallow boreholes was installed in the alluvial aquifer in 1994 and groundwater sampling runs commenced in 1995. Groundwater occurs in the region in a shallow alluvial aquifer and a deeper fractured secondary aquifer. These aquifers are separated from one another by an impermeable, confining layer of Cretaceous sediments in the central and eastern parts of the study area, causing artesian conditions in places. The groundwater of the aquifers in the study area has a sodium-chloride character of low salinity in the western high-lying portion of the study area, with mineralisation increasing eastward, as aquifer lithology and distance from recharge sources change. The hydrochemical character of the groundwater is a function of the proximity of the basin to the sea, as well as connate conditions existing in the sediments of marine origin. It is shown that pollution of both the surface and shallow sub-surface water bodies is occurring, mainly in the industrial and residential areas of Uitenhage and Despatch. These polluted zones are not extensive when compared with the whole catchment area but have a definite effect on local conditions. Estimations of pollution load volumes are made based on hydraulic parameters derived from aquifer tests. This study represents an overview of the geohydrology of the Swartkops River Basin, thereby providing a reference tool for water-resource management purposes in the region. It includes a unique study on the geohydrology of the Swartkops River Alluvial Aquifer and the extent of pollution of this aquifer, as well as a detailed account and discussion on the historical and present factors affecting variations in groundwater flow and artesian conditions in the area. A summary of suggested aquifer management practices is given to ensure the long-term sustainability of the groundwater resources of the river basin.